PEMBELAJARAN MATEMATIKA STRATEGI QUANTUM LEARNING UNTUK MENINGKATKAN MOTIVASI BELAJAR SISWA - Sukamto Sukamto (Malih Peddas (Majalah Ilmiah Pendidikan Dasar), 2014)
This study in the background backs low student motivation, especially elementary school mathematics subject matter. Mathematics courses is one of the lessons learned from the primary school level. Even informally parents have taught mathematics to the toddler through the tools of play. Elementary students have thought of mathematics courses is subject scary and considered difficult. Mathematics courses are eye pelajarana considered difficult for students, student motivation to learn a low, monotonous learning process, uninteresting and boring for students. Students in participating in math do not wholeheartedly and only keterpaksaaan alone. Conditions like these that lead to low mathematics achievement.One of the characteristics of mathematics is to have an abstract object and became one of the difficulties faced by both teachers to teach and students in understanding it. Teachers as educators should be aware that elementary school students still think concretely. This causes the teacher should try to reduce the abstract nature of mathematical objects so as to facilitate the students understand the subject matter, but still directed towards the achievement of learning abstract thinking ability of students. Elementary school students still think concretely, it is easy to understand if it can be detected by the senses. Learning strategies should be able to maximize all potential, every student has the same right to succeed. All the elements that underpin the success of learning should be mixed into an accumulation that really create a learning atmosphere. Some of the techniques used is to give positive suggestions with seats the students are comfortable, put background music in the classroom, increasing the participation of individuals, using posters to give a great impression while highlight information (DePorter, 2005: 14). Thus we can conclude quantum mathematics learning strategy learning can increase students' motivation.